Implementation of Contractor Safety Management System as a Requirement for Partners at a Petrochemical Company - Yuliana Duwi Kusuma Wardhani (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Data Report Safety Performance Indicator for Oil and Gas Producers (OGP) in 2018 recorded 2 deaths at the company and 29 deaths occurred to the contractors, with Fatal Accident Rate (FAR) in the company of 0.31 accidents per 1 million working hours and in contractors of 1.20 accidents per 1 million work hours. PT Pupuk Kujang as a petrochemical company has a high-risk of implementation of Contractor Safety Management Systemn (CSMS) to protect safety of contractors. This research aims to evaluate the implementation of Contractor Safety Management System (CSMS). Methods: This study was a descriptive study with an observational method for data collection, and this study was cross-sectional. The variable studied was Contractor Safety Management System (CSMS) including CSMS stages and documents. Results: PT Pupuk Kujang has implemented six stages for the implementation of Contractor Safety Management System (CSMS), namely identification and risk assessment, prequalification, selection, initial work activities, assessment during work, and final assessment of work. However, some shortcomings were observed in the implementation of pre-qualification stage where before being declared to have passed the pre-qualification assessment stage, a local contractor has been appointed as the winner of the tender. Conclusion: The implementation of Contractor Safety Management System (CSMS) at PT Pupuk Kujang still does not run well because there are deficiencies in the prequalification stage.Keywords: contractor safety management system, pt pupuk kujang, prequalification